Plastic responses for intercrop functioning - Franca J. Bongers; Jochem B. Evers; Niels P. R. Anten (npj Sustainable Agriculture)
Abstract Intercropping systems have large heterogeneity in canopy and soil conditions, which could induce phenotypic plasticity. We review different kinds of observed plasticity and to what extent these influence crop performance and outline the diversity of signals that could occur in intercrops. Studying how plasticity is induced and quantifying the consequences for intercrop performance are relevant to better understand the consequences of mixing species and provides leads for breeding for intercrops.